Vesico-vaginal fistula post Right radical nephroureterectomy with bladder cuff excision - Poudel, R; Dangal, G; Karki, A; Pradhan, H; Shrestha, R; Bhattachan, K; Bajracharya, N; Tiwari, K (Nepal Journal of Obstetrics and Gynaecology, 2018)
Case: 61 years, female presented at KMH OPD with involuntary urinary leakage per vaginum for seven months following Right radical nephreureterectomy with bladder cuff excision for urinary bladder carcinoma at other centre. Dye test was positive. Cystoscopy revealed VVF defect around 2 cm (Goh’s stage 3biii) at right posterior wall of urinary bladder. Ureteric catheter was placed in left ureter and VVF repair was done. Dye test following 14 days of Foley’s catheterization was negative and patient went home dry. We present here a case of successful repair of VVF following Right radical nephreureterectomy with bladder cuff excision. Key words: dye test, Goh’s stage, pelvic surgeries, urinary tract injuries, vesico-vaginal fistula